Introducing Ce ions and oxygen vacancies into VO2 nanostructures with high specific surface area for efficient aqueous Zn-ion storage - Mingying Bao; Zhengchunyu Zhang; Xuguang An; Baojuan Xi; Shenglin Xiong (ChemPhysMater)
Positive electrodes play a decisive role in exploring the Zn2+ storage mechanism and improving the electrochemical performance of aqueous Zn-ion batteries (AZIBs). Feasible design and preparation of cathode materials have been crucial for AZIBs in recent years. Herein, taking the advantage of the tunnel structure of VO2, which can withstand volume change during charging/discharging, VO2 doped with Ce ions is synthesized by a simple one-step hydrothermal method and oxygen vacancies are synchronously generated during synthesis. It delivers a capacity of 158.5 mAh g−1 at the current density of 5 A g−1 after 1000 cycles and exhibits an excellent energy density of 312.8 Wh kg−1 at the power density of 142 W kg−1. The structural modification and prospect of enhancing its conductivity by doping with rare-earth metals and introducing oxygen vacancies may aid in improving the stability of AZIBs in the future.